A Rare Complication of Endovascular Embolization: Extruded Onyx on Trigeminal Nerve - Eser Ocak, Pinar; Başkaya, Mustafa Kemal (Journal of Neurological Surgery Part B: Skull Base, 2018)
Objectives To demonstrate a rare complication of endovascular tumor embolization with onyx.Design Operative video.Setting Department of neurological surgery in a university hospital.Participants A 39-year-old male who was diagnosed with a right sided hemangioblastoma.Main Outcome Measures Surgical resection of the tumor, preservation of the cranial nerves and extruded embolization material on trigeminal nerve.Results The tumor was embolized with onyx the day before surgery. Patient woke up with no sensation in the right side of his face. Diffusion magnetic resonance imaging (MRI) showed a small restricted diffusion area within the right superior cerebellar vermis. Microsurgical resection of the tumor was uneventful and complete resection was achieved (Fig. 1). After the resection was completed, the trigeminal nerve was identified. Some of the capillaries overlying the nerve as well as the cerebellum and brain stem had extruded onyx-embolic material (Fig. 2). Some of the onyx over the cerebellum was removed; however, the ones on the trigeminal nerve and brain stem were not removed due to the risk of injury to the nerve. Postoperative MRI confirmed total resection. Patient made excellent recovery except he continued to have no sensation in the right side of his face.Conclusion Preoperative embolization is an important adjunct to resection of large hemangioblastomas in selected cases because it may facilitate circumferential dissection and debulking of the tumor. Although extrusion of the embolization material is relatively common, immediate extrusion of onyx and its transfixion on a cranial nerve has not been reported before. Judicial selection of preoperative embolization is required in hemangioblastomas.The link to the Video can be found at: https://youtu.be/s0DjD26Xkas.
Keywords: cerebellopontine angle; onyx; embolization; trigeminal nerve; hemangioblastoma